UNRAVELLING THE FACTORS THAT IMPEDE STUDENTS’ ENGLISH LANGUAGE LEARNING: FROM TEACHERS’ VIEWPOINT - HUSSAIN AHMED LITON (Innovare Journal of Social Sciences, 2024)
Students’ effective learning and course learning outcomes (CLOs) are of constant concern for teachers, students, parents, and institutions, regardless of academic levels and contexts. To this end, teachers employ varied techniques and methods in soliciting the expected learning outcomes and students’ academic skill developments, but very often some factors are found to be liable and barriers to the success of this mission. Behind such a teaching and learning perspective, this paper attempts to explore the factors that impede students’ English language learning (ELL) and CLOs at Jazan University, Saudi Arabia, with the intent of finding new vantage points that augment students’ effective learning outcomes. To this end, the present study devised a survey questionnaire for teachers (Appendix 1) to collect data and observations to determine the ground reality of the issue undertaken for this study. The population participants were 25 EFL teachers. The collected data were analyzed qualitatively. Finally, the analytical result of this paper unveils that teachers should drive “needs analysis” to diagnose the learners’ lack of motivation, TBLT practice in the classroom, and their training for techno-pedagogical professional skill development. It also reveals some other implications and effective recommendations for making a learnercentric EFL teaching and learning curriculum. The findings of this paper contribute to the fields of ELT, TEFL, learning outcomes, curriculum design, pragmatics, and ELL paradigms.